2006
DOI: 10.1590/s0034-72992006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Processamento auditivo em indivíduos com epilepsia de lobo temporal

Abstract: A epilepsia do lobo temporal ocasiona descargas elétricas excessivas onde a via auditiva tem sua estação final. É uma das formas mais comuns e de mais difícil controle da doença. O correto processamento dos estímulos auditivos necessita da integridade anatômica e funcional de todas as estruturas envolvidas na via auditiva. OBJETIVO: Verificar o Processamento Auditivo de pacientes portadores de epilepsia do lobo temporal quanto aos mecanismos de discriminação de sons em seqüência e de padrões tonais, discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(65 reference statements)
0
5
0
4
Order By: Relevance
“…The temporal lobe epilepsy was a factor that differentiated sound processing, whereas, individuals with this change showed impairment in the ability to analyze verbal and nonverbal sounds received auditorily. This cortical region is responsible for processing acoustical information 24 .…”
Section: Temporal Aspects Of Auditionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal lobe epilepsy was a factor that differentiated sound processing, whereas, individuals with this change showed impairment in the ability to analyze verbal and nonverbal sounds received auditorily. This cortical region is responsible for processing acoustical information 24 .…”
Section: Temporal Aspects Of Auditionmentioning
confidence: 99%
“…For a proper analysis and interpretation of information received auditorily (auditory processing) it is required anatomical and functional integrity of these structures. The electric discharges caused by seizures can cause neuronal loss in the region where the auditory processing occurs, these arose the hypothesis that there are difficulties to process mental information received auditorily, which might worsen the communication skills of these patients 24 .…”
Section: Temporal Aspects Of Auditionmentioning
confidence: 99%
“…Anatomical and functional integrity of the auditory pathways, from peripheral to central structures, is essential for proper processing of auditory stimuli and a satisfactory development of language, speech, and learning [1].…”
Section: Introductionmentioning
confidence: 99%
“…1 Auditory processing is the term used to describe what happens when the brain recognizes and interprets the sounds around a person 2 ; and auditory processing disorder refers to a difficulty in the perceptual processing of information in the Central Nervous System, shown by a low performance in one or more hearing skills, such as location, lateralization, auditory discrimination, auditory pattern recognition, temporal processing deficits and others. 3 Thus, auditory processing and auditory processing disorders have been broadly studied in a variety of clinical studies [4][5][6][7][8] ; however, very few reports are found in relation to central auditory function in the population with labio-palatine fissure. It is the large occurrence of otologic problems and the consequent peripheral hearing loss that have been stressed in those people with this congenital malformation.…”
Section: Introductionmentioning
confidence: 99%